Validating the Chinese-translated version of the Spiritual Health and Life-orientation Measure (SHALOM) amongst the Chinese youth populations in 2010 and 2018 - Pong, Hok-Ko (Journal of beliefs and values, 2020)
This cross-sectional study validated the Chinese-translated version of the Spiritual Health and Life-orientation Measure (SHALOM) in two samples of university students in Hong Kong. The first sample comprised 546 Chinese university students who were educated under the old educational system (i.e. 3 + 2 + 2 + 3 scheme) and are known as ‘Generation Y’. Data for this sample were collected in 2010 for Fisher and Wong. The second sample involved 474 Chinese university students educated after educational reform in 2009 (i.e. 3 + 3 + 4 scheme) collected in 2018. Results in both years revealed high internal consistency. Whereas the SHALOM model proposes four domains of spirituality (personal, communal, environmental and transcendental), exploratory and confirmatory factor analyses indicated that a three-factor model provided the best fit to the data, with the personal and communal domains combined as one domain. This three-factor model was identified in both the 2010 and 2018 samples, and in both males and females. Findings indicated that compared to non-religious participants, religious participants had significantly higher scores in the transcendental domain of spiritual health on both the ideal values and lived experience subscales. The results are discussed in relation to Confucian philosophy. Future research on the spiritual health of youth in Hong Kong is suggested.